Personality and willingness towards performance enhancement and body modification: A cross-sectional survey of a nationally representative sample of Norwegians - Breivik, Gunnar; Sagoe, Dominic; Loland, Sigmund (Frontiers in Sports and Active Living, 2022)
We conducted an exploratory investigation of the relationship between personality and willingness towards performance enhancement and body modification in Norway. The study is based on Norwegian Monitor data from a cross-sectional survey of a nationally representative sample of 4,233 (females: 49.9%) persons aged 15 to 96 (45.92 ± 18.02) years. Data were collected using a questionnaire containing demographic questions and measures of physical appearance satisfaction, physical activity level, personality (five-factor model), and willingness towards performance enhancement (e.g., substances that improve creative thinking) and body modification (e.g., use of muscle-building substances). Data were analyzed using descriptive statistics and multiple regression analyses. We found that 62.2% and 50.1% of our sample were either willing to use or contemplating using substances that reduce memory failure and enhance physical fitness respectively. Our sample was most willing or contemplating tattooing (30.0%) and generally skeptical of the other body modification methods with willingness to use or contemplating using substances to enhance muscularity least accepted (3.9%). Higher fantasy/openness and lower agreeableness were associated with higher willingness towards both performance enhancement and body modification. Additionally, higher extraversion and lower control/conscientiousness predicted higher willingness towards body modification. Our findings corroborate previous indications that performance enhancement and body modification are now mainstream. They also underline the importance of personality traits in willingness towards these practices.